3D multiscale tri-level finite element analysis of aluminum matrix composites with Nano&Micro hybrid inclusions. (1st February 2023) - Peng, Yahui; Zhao, Haitao; Ye, Jinrui; Yuan, Mingqing; Tian, Li; Li, Zhiqiang; Liu, Yang; Chen, Ji'an
Abstract: In this paper, a novel multiscale tri-level finite element (FE) numerical analytical method is proposed to study the mechanical performance of SiCp/CNT dual-scale hybrid reinforced aluminum matrix composite materials. The analysis is ranging from nano-scale CNT reinforcement to micro-scale SiCp particles to macro-scale composite systems. The microstructures of the CNTs and 6061Al matrix at the nano-RVE and the SiCp particles, interfaces, and 6061Al matrix at the micro-RVE are established. At the macro-scale, the structural model is established, whose elastic–plastic material properties and damage state are derived from the homogenization calculation of the representative volume element (RVE) at the micro-scale. Multi-scale progressive damage simulation of the macro-scale model is achieved by invoking the micro-scale and nano-scale RVE. The stress–strain curve of one finite element in the macro-structure model is randomly extracted and comparing it with the calculated micro-material-properties of SiCp (CNT)/ 6061Al, the good consistency verifies the effectiveness and accuracy of the multi-scale tri-level FE calculation method proposed in this paper. Using this multi-scale tri-level FE model, we can see the load-bearing and fracture process of the macrostructure, and the damage evolution process of the microstructure, which enables us to further carry out the research work of composite microstructure design, interface regulation, etc.